Ricoeur em Coimbra: Receção filosófica da sua obra - Maria Luísa Portocarrero e José Beato (Ideia, 2016)
At the occasion of the Paul Ricoeur's centenary this volume joined in tribute several scholars, young researchers, and Ph.D students around the main themes that marked the reception of the philosopher's work in Portugal and, especially in the University of Coimbra. Each chapter demonstrates the vigour Ricoeur's thought as it is rooted in the "reflexive tradition", as it assumed the "existentialist" horizon, as it articulated Phenomenology and Hermeneutics. This philosophical project as, today, an enormous range of influence. This is a project that promotes dialogue between disciplines, authors, and cultures, overcoming theoretical divisions in face the demands of praxis. From this rich and plural inspiration comes the ability to meet with other fields of thought, namely psychotherapy, history, neuroscience, bioethics, social sciences, and literary studies.